Canine Pyometra: Clinico-diagnostic, Microbial, Gross and Histopathological Evaluation - Hadiya, Hardik D.; Patel, Dipak M.; Ghodasara, Dinesh J.; Bhanderi, Bharat B. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The study aimed to categorize clinical signs, diagnostic efficacy of different techniques, and microbiological and pathological findings ofcanine pyometra. The study covered total 18 bitches; ten with pyometra and eight healthy ones presented for spaying. All the bitches withpyometra were found lethargic, dull, and depressed. The general condition of bitches with closed pyometra (n=2) was poor, whereas itwas fair in cases of open pyometra (n=8). The mean rectal temperature of bitches with pyometra was 102.67±0.18 ºF. Vomition, polyuria,polydipsia, and diarrhea were recorded in 40, 40, 60 and 10 % pyometra cases, respectively. The age of affected bitches was 4 to 12years with a mean of 8.8±0.71 years. The prevalence of pyometra was higher in nulliparous animals (5 cases) followed by multiparous(4 cases) and primiparous (1 case) bitches. The abdominal palpation was clear for pyometra in only 20% of cases. Radiography was clearin 40% of cases, whereas ultrasonography was clear and confirmatory in 100 % of cases. Uterine content of all ten cases of pyometrawas positive for bacterial isolates; mostly Gram-negative bacilli (50%) followed by gram-positive cocci (30%) and mixed isolates (20%)as against sterile contents of healthy bitches. Amoxycillin was the most effective antibiotic (60.00 %) against bacterial isolates followedby amikacin and gentamicin (50.00 % each). Grossly, the mean weight of intact reproductive organs of bitches with pyometra was987.5±317.61 g as against 77.50±23.83 g in normal healthy bitches. The mean length of right and left uterine horns was almost doublethan in healthy bitches, and it varied from 10 to 53 cm in pyometra cases. The colour of uterine content was found variable in casesof pyometra from greyish to dark brownish with watery to thick consistency. There were presence of CLs, cysts or follicles on either ofthe ovaries in majority of bitches with pyometra. The histopathological changes of uterine tissues after ovario-hysterectomy indicatedclassical pyometra.
Keywords: Canine pyometra; Predisposing factors; Clinico-pathology; Diagnosis; Histopathology